Faktor-faktor yang mempengaruhi peningkatan minat masuk seminari - Diri, Ardianus; Mani, La; S. Hasanah, Rosiana; Hidayat, Z. (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Seminary is an educational place (dormitory and school) which is devoted to children who have the desire to become priests. These young people are nurtured by the teaching staff of the priests. This study aims to examine the influence of seminary promotion factors, student religiosity, social media and students' understanding of seminary so that they are interested in joining the seminary. Quantitative research was conducted using a survey method by distributing questionnaires to 100 generation Z students of SMP Panca Setya 2 Sintang from January 2021 to April 2021. The results showed that seminary promotion and social media had a significant effect on understanding and interest in seminary. However, student religiosity has no significant effect on interest in entering the seminary. Conclusion: Interest in entering seminary is influenced by seminary promotion, social media and students' understanding of seminary. Therefore seminaries need to increase promotion of seminary, social media and understanding of Generation Z students about seminary in an effort to increase student interest in entering seminary.